Ice/cold Stimulation on Post-stroke with Dysphagia: A Systematic Review - Rongqing LI; Wenying LIN; Jinxiu CHEN; Zhuangmiao LI (康复学报)
Objective:To evaluate the intervention of ice/cold stimulation on post-stroke with dysphagia.Methods:The Cochrane Library, EMbase, Web of Science, PubMed, CBM, Wanfang Data, CNKI and VIP database were searched for the randomized controlled trials (RCTs) about the effects of ice/cold stimulation on post-stroke with dysphagia, from the dates of establishment of the databases to December 31, 2016. The data were analyzed by RevMan 5.3 software.Results:Totally 25 literatures of RCTs including 1, 936 patients met the inclusion criterion. The results of meta-analyses showed that the total effective rate was not affected by the means of ice/cold stimulation and duration, the total effective rate of the intervention group was higher than that in the control group, with statistical significance (P<0.05), swallowing disorder functional score [SMD=-1.91, 95%CI (-2.48, -1.34), P<0.000 01], the prevalence rates of aspiration pneumonia [RR=0.30, 95%CI (0.18, 0.48), P<0.000 01] and malnutrition [RR=0.27, 95%CI (0.09, 0.77), P=0.01] in the intervention group was lower than that in the control group, and the difference was statistically significant (P<0.05).Conclusion:Ice/cold stimulation on post-stroke with dysphagia can improve the swallowing function, and can reduce the prevalence rates of aspiration pneumonia and malnutrition. However, due to the quality and quantity of inclusive studies is limited, the aforementioned conclusion still needs further confirmation by more rationally designed RCTs with large samples to verify.